Direct-to-consumer misleading information on cancer risks calls for an urgent clarification of health genetic testing performed by commercial companies. (June 2020) - de Pauw, Antoine; Schwartz, Mathias; Colas, Chrystelle; Golmard, Lisa; Stoppa-Lyonnet, Dominique
Abstract: Direct-to-consumer (DTC) commercial companies offer genetic tests that are presented as allowing individuals the opportunity to increase their capacities to be in charge of their own healthcare managements. DTC companies deny performing medical tests, yet they provide data based on sequencing multigene panel or whole exome. This contradiction allows these companies to escape the requirements of a regulated medical practice that guarantees the quality of the tests, as well as the information and support for tested individuals. Herein, we illustrate the lack of such requirements by analysing the bad experience of a young man who dealt with DTC health genetic testing companies. There is an emergency for DTC testing to be either deprived of any medically relevant information, or carried out in a legally regulated medical framework. Highlights: By blurring the lines between commercial 'health' products and medical information, direct-to-consumer (DTC) companies are de facto performing medical tests. Health professionals and the general population need to be aware of the significant limitations of DTC genetic health tests. No medical decision should be taken on the basis of genetic results obtained outside of a legally regulated framework. If DTC companies perform medical tests, they have to be carried out in a regulated framework guaranteeing their quality.